EFFICACY OF LOCAL THERAPY OF MYCOTIC LESION OF TONSILS IN CHILDREN - Yu.L. Soldatskiy; E.K. Onufrieva; N.V. Shchepin; A.M. Steklov; S.F. Gasparyan; S.N. Popova (Union of pediatricians of Russia, 2011)
Fungal infection of tonsils (tonsillomycosis) is a common disorder in childhood. In this paper we analyzed the clinical efficacy of topical aerosol containing gexetidin, possessing both antimicrobial and antimycotic activity, as compared with conventional topical antifungal therapy of tonsillomicosis in children. According to the study, the clinical efficacy of the investigated product is comparable to the conventional treatment, but the therapy firepower was significantly higher with gexetidin aerosol. The obtained results allow to recommend an aerosol containing gexetidin for widespread use in the treatment of inflammatory diseases of the oropharynx, including fungal nature. Key words: gexetidin, tonsillomicosis, treatment, children. (Pediatric Pharmacology. - 2011; 8 (5): 42-45.)